The Role of the British East India Company (EIC) in the Collapse of the Mughal Empire From Trade Competition to Political Domination - Solehudin, Solehudin; Nurcahya, Yan; Basor, Saepul; Suprianto, Sopian (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2025)
The aim of this research is to determine the influence of the British EIC (East India Company) on the process of the collapse of the Mughal Empire, researching from the economic stage to the political field in the Indian subcontinent. This article uses qualitative research of a library nature. Library research uses library data, as well as analysis of each source. After collecting several sources, it emerged that the British with their EIC controlled India starting with controlling trade in all strategic areas of the Indian subcontinent as well as collaborating with local residents, and influencing the rulers to obtain more facilities and trade monopoly opportunities. Then, after the rise of the EIC Economy, the next step was to slowly control politics by influencing local regional policies up to the Mughal Empire and carrying out divisive politics in order to prioritize the position of the EIC in India. So it can be concluded that the EIC was the starting point for imperialism in the Indian subcontinent, from economic control to political influence.